The MANIPULATIVE NATURE OF MEDIA-POLITICAL DISCOURSE - Gasparyan, Seda; Harutyunyan, Rafayel (Armenian Folia Anglistika, 2022)
At the present moment, media saturation provides us with a reasonably objective criterion available for examination. In a loose sense, the Internet has become a parallel reality where people live to pursue constantly updated news at the repeated click of a button, which maintains the reader’s immediate interest in every sense of the word. In perusing news articles, placing a particular emphasis on their manipulative nature, we can plunge deeply into such language layers as that of the lexical, grammatical, stylistic, etc. In this paper we place our central interest on the lexical aspect of language manipulation because words are the foundation of meaning in speech. A functional-communicative view of the lexical material of the discourse of news articles reveals the effect of a journalist’s choice and arrangement of words on the reported news and how the manipulative potential of language unfolds.